Qualtric Effect of TQM, Market Competitiveness, Organizational Innovation and Firm Performance - Herminawaty Abubakar; Iwan Perwira; Hasanuddin Remmang; Seri Suriani; Thanwain Thanwain; Nur Naninsih (STMIK Dharma Wacana, 2022)
Global competition is getting tougher, forcing companies to continue to improve the quality of the products or services they produce and improve company performance to compete well in the global market. In the property business, companies must pay attention to the quality of project development, after-sales service, and building aquality and maintain a good company reputation (Caby et al., 2020). Global competition is getting tougher, forcing the Indonesian government to improve its infrastructure to attract foreign companies and investment. Good infrastructure development can improve people's quality of life and provide better job opportunities, which can help economic growth (Amoako-Gyampah et al., 2019). Good infrastructure development can also increase the demand for property because the demand for residential and commercial property will increase along with the increase in population and the need for business development. Pro-business government policies and the tax amnesty program offered by the government can also improve public interest in investing in the property sector, thereby increasing the sector's growth.